1382. A Prospective Epidemiological Study BK Polyomavirus DNAuria and DNAemia within the First Year after Kidney Transplantation. (4th December 2021) - Mongkolrattanakul, Pannawat; Bruminhent, Jackrapong; Siripoon, Tanaya; Wiwattanathum, Punlop; Worawichawong, Suchin; Kantachuvesiri, Susarak
Abstract: Background: Screening and early detection for the preceding BK polyomavirus (BKV) DNAuria and DNAemia to prevent the occurrence of BK polyomavirus BKV-associated nephropathy (BKPyVAN) among kidney transplant (KT) recipients has not been universally utilized and never assessed in a setting where the resource is limited. Therefore, we aimed to investigate this entity's incidence, risk factors, and outcome with this intervention at our institution. Methods: A prospective study of KT recipients at a tertiary care transplant center in Bangkok, Thailand, was conducted between January 2019 and March 2020. All patients underwent preemptive monitoring of urine and plasma BKV DNA load, measured by quantitative real-time PCR at 1, 2, 3, 6, 9, and 12 months post-KT. Low- and high-level BKV DNAuria was defined as urine BKV DNA load of < and > 7log10 copies/mL, respectively. Low- and high-level BKV DNAemia was defined as plasma BKV DNA load of < and > 4log10 copies/mL, respectively. The incidences were calculated by Kaplan-Meier analysis. The chi-square or student's T-test compared clinical characteristics between those with and without high-level BKV DNAuria as appropriate. Risk factors of high-level BKV DNAuria were analyzed using Cox proportional hazard model. Results: Among 99 evaluable KT recipients, a mean (SD) age was 42 (11) years, 64.6% were male, and 69.6% received an induction immunosuppressive therapy. Within 12 months post-KT, the incidences of low-level BKV DNAuria, high-level BKV DNAuria, low-level BKV DNAemia, and high-level BKV DNAemia were 22.63%, 13.14%, 9.49%, and 5.11%, respectively. High panel reactive antibody (PRA) was associated with high-level BKV DNAuria at 6 and 12 months, (HR 1.02 [95% CI (1.00-1.04)], P=0.019) and (HR 1.02 [95% CI (1.00-1.04)], P=0.023), respectively. Underlying diabetes mellitus was associated with high-level BKV DNAuria (HR 3.49 [95% CI (1.28-9.51)], P=0.015) at six months; however, not at 12 months. There was no allograft rejection directly related to a reduction of immunosuppression for BKV infection observed. Conclusion: BKPyV infection is also prevalent among KT recipients in a resource-limited setting, however, without unfavorable consequence. Those with high-level PRA and underlying diabetes could be at risk of high-level BKV DNAuria after KT. Disclosures: All Authors : No reported disclosures